INDICATORS OF THE ANALYSIS OF THE FINANCIAL CONDITION OF THE ENTERPRISE (World Economics and Finance Bulletin, 2025)
The article examines the theoretical aspects of analyzing the financial condition of an enterprise, namely the concept, essence and indicators of analyzing the financial condition of an enterprise. Various research methods have been used, and a lot of literature has been studied in the field of the research topic. The theoretical significance of the research lies in the systematization of approaches to the disclosure of the economic content of the concept of “financial condition”, as well as in the theoretical analysis of methods for analyzing the financial condition of an enterprise